PCB-related exposure and effects in ringed seals (Pusa hispida) frequenting a locally-contaminated marine environment in Labrador - Brown, Tanya (2014)
The release of 260 kg of polychlorinated biphenyls (PCBs) by a military radar station into Saglek Bay (Labrador) in the eastern Canadian Arctic contaminated adjacent marine sediments, and some fish, seabirds, and ringed seals. However, attributing the PCBs found in high trophic level and highly mobile marine mammals to any point source is, in most cases, impossible. This thesis demonstrated the extent to which a local PCB source at Saglek Bay led to the contamination and health effects in ringed seals. The dominance of PCBs at this contaminated marine site afforded a unique opportunity to evaluate the effects of this single class of industrial chemical in a manner that has not been previously possible in marine mammals. We used a variety of tools to characterize the contribution of local PCB contamination in the Labrador ringed seal food web. These tools included: 1) univariate and multivariate statistical exploration of contaminant patterns; 2) stable isotope ratios and fatty acid signatures to describe feeding ecology; and 3) satellite telemetry to track the movements of seals on the coast. Divergent PCB congener profiles and contaminant ratios enabled an assignment of seals into either ‘local’ or ‘long-range’ categories, with up to 60% of ringed seals sampled exhibiting patterns consistent with the local source. PCB concentrations in locally-contaminated adult males were 2-fold higher than in those exposed only to long-range PCB sources. Seals with smaller home ranges had an increased likelihood of feeding on prey contaminated by the local PCB source. Similar fatty acid profiles between those seals with ‘local’ PCB profiles and those with ‘long-range’ or background profiles indicate little support for the possibility that differential feeding ecologies explained the divergent PCB profiles. Ringed seals fed predominantly on zooplankton (Mysis oculata and Themisto libellula), dusky snailfish (Liparis gibbus) and arctic cod (Boreogadus saida). Heavier PCB profiles in the Saglek food web, compared to the same ...